Rezension von: Lister, Adrian; Bahn, Paul, Mammuts - Eilders, Hauke (Württembergisch Franken, 1999)
Adrian Lister u. Paul Bahn, Mammuts. Riesen der Eiszeit (Thorbecke Species, Bd. 1), Sigmaringen (Thorbecke) 1997. 168 S., zahlr. Abb.